Managing irrigation under pressure: how supply chain demands and environmental objectives drive imbalance in agricultural resilience to water shortages - Sutcliffe, Chloe; Knox, Jerry W.; Hess, Tim M. (Elsevier, 2020)
Food production systems worldwide are increasingly exposed to water shortage shocks. Social-ecological resilience theory provides insights into the qualities which confer production systems with the capacity to absorb shocks and persist, undertake adaptations and ultimately achieve desirable transformations. Combining findings from the analysis of a set of 15 semi-structured interviews and 92 survey responses from growers in the UK, this paper uses resilience theory to explore the factors affecting exposure to the risk of water shortages, and management responses, within outdoor field vegetable production systems that depend on supplemental irrigation. The findings confirm that growers predominantly aim to build resilience by seeking to maintain a buffer or ‘headroom’ in their water resources to minimise the possibility that a shortage will disrupt their output of marketable produce and/ or lead to financial loss. This buffering strategy confers robustness by increasing system redundancy (availability of spare resources). But building-in redundancy conflicts with regulatory and supply chain pressures to maximise water and production efficiency respectively. Whilst stability of supply to consumers is, for the most-part, achieved, the discrepant pursuits of robustness and efficiency lock agricultural systems into increasingly rigid production and sales pathways, limiting capacities for adaptation and transformation - dimensions of resilience which permit successful system evolution in the context of more extreme shocks and stresses
Keywords: water resources; transformation; adaptation; drought; food